Exploration of the implementation of direct observation of procedural skill as an instrument for evaluation of clinical skills in dental professional education: Eksplorasi implementasi direct observation of procedural skill sebagai instrumen evaluasi keterampilan klinis pendidikan profesi kedokteran gigi. - Natalia Putri Handayani; Sri Linuwih Menaldi; Estivana Felaza (Makassar Dental Journal PDGI Makassar, 2022)
Clinical phase of medical education includes understanding theory, mastery of skills and affective learning. The learning pro-cess were evaluated using a workplace-based assessment (WBA) approach. Direct observation of procedural skill (DOPS) was one of the WBA assessment methods. This research used qualitative methods with a phenomenological approach. The study po-pulation were clinical supervision lecturers and students of the clinical phase. The research method began with the pre-research stage; training for lecturers on how to implement DOPS, followed by the research stage; document study, observation, and focus group discussion (FGD). The results of the study found three major themes, namely concepts, ways of implementing, and obs-tacles to implementing DOPS. According to the teaching staff and students at FKG UK Maranatha, DOPS was an assessment of student procedural skills by direct observation of each stage of the procedural work. The teaching staff's perceptions about DOPS affected the way lecturers provide feedback to participants. As conclusion, full observation is needed to generate useful feedback for students. The effectiveness of DOPS is influenced by the availability of patients, the presence of examiners, and the availability of sufficient time to run DOPS.